PERSEPSI DAN SIKAP NASABAH DALAM MEMPEROLEH KREDIT USAHA AGRIBISNIS PADA BANK KONVENSIONAL DAN BANK SYARIAH - Himatus Sholihah; Syarif Imam Hidayat; Nuriah Yuliati (University of Jember, 2014)
This research is aimed to analyze customer perception and trust in getting agribusiness loans from conventional and syariah banks and discovering efforts that had been and should be done by those financial institutions. Descriptive analysis is used to accomplish first and third purpose and multiatribut fishbein analysis is used to accomplish the second purpose. Conventional banks have better customer perceptions than the syariah due to its wide network, easier loan procedures. Clearer operational systems, simple and easy to understand and good payment opportunities. Customers have a greater trust to convensional banks than the syariah since convensional banks are better known by agribusiness people. Not only did the conventional banks make the effort to add and enlarge branch offices both in the cities and in villages, they also made the loan procedure more simple, easier and faster to get. Whilst the syariah banks are the other and they hire people from conventional banks. Either conventional or syariah banks should conduct the SOP audit as internal control so the bank can work effectively, efficiently, safely, economically, orderly for the improvement of banks performance. Keywords: perception, trust, customer conventional and syariah banks, loans agribusiness